2001
DOI: 10.1080/07315724.2001.10719183
|View full text |Cite
|
Sign up to set email alerts
|

Can Dietary Methionine Restriction Increase the Effectiveness of Chemotherapy in Treatment of Advanced Cancer?

Abstract: Most metastatic tumors, such as those originating in the prostate, lung, and gastrointestinal tract, respond poorly to conventional chemotherapy. Novel treatment strategies for advanced cancer are therefore desperately needed. Dietary restriction of the essential amino acid methionine offers promise as such a strategy, either alone or in combination with chemotherapy or other treatments. Numerous in vitro and animal studies demonstrate the effectiveness of dietary methionine restriction in inhibiting growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…These intriguing observations led to an examination of the effect of dietary methionine restriction, including in combination with chemotherapy, on tumor growth in xenograft models of human cancer (13,14). Efficacy was shown in these models, and synergism was produced by adding chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…These intriguing observations led to an examination of the effect of dietary methionine restriction, including in combination with chemotherapy, on tumor growth in xenograft models of human cancer (13,14). Efficacy was shown in these models, and synergism was produced by adding chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a rat colon cancer model, for example, MR has been shown to inhibit the formation of preneoplastic aberrant crypt foci after the administration of the carcinogen azoxymethane [9]. Data from a phase I clinical trial conducted on 8 patients with metastatic solid tumors by Epner and colleagues indicated for the first time that diet with a reduced Met content is safe and feasible to treat patients with cancer, despite a conclusive lack of sufficient anti-tumor activity [10,11]. A Met-free diet was used in con-junction with other anti-cancer agents in another two Phase I clinical trials [12,13].…”
Section: Methionine Restriction In Aging and Can-cer Studiesmentioning
confidence: 99%
“…In a recent study using fruit fly Drosophila melanogaster, the addition of Met to a CR diet reduced life span and this reduction in life span could be avoided by simply removing Met from the diet [3]. Both nutritional interventions, CR and methionine restriction (MR), do not only simply extend life span, but also forestall the onset of a variety of age-related diseases, such as cancers, obesity, diabetes, hypercholesterolemia and more [3,4,6,[9][10][11]. Since the etiology of many types of diseases involves collapse of epithelial and/or endothelial barriers [4], it is reasonable to speculate that either CR or MR, at least in part, exert their benefits through strengthening barrier functions.…”
Section: Methionine Restriction In Aging and Can-cer Studiesmentioning
confidence: 99%
“…Levels of cysteine, homocysteine, cysteinyl-glycine and glutathione were determined in plasma from tumour-bearing mice (days 1,3,5,8,10) and from healthy mice (control). Results are presented in Figure 4b.…”
Section: Temporal Evaluation Of Metabolites In Blood Plasmamentioning
confidence: 99%
“…Since this phenotype is unique to cancer cells, it has been proposed as a selective target for cancer therapy. 6,8,9 Although aspects of methionine metabolism have been studied in attempts to identify the underlying mechanism of this metabolic defect, the biochemical mechanism of methionine dependence is not fully understood.…”
mentioning
confidence: 99%